Vinculação materna no puerpério - Souza, Lara Helk de (2014)
Introduction: The maternal bonding is an adaptation process between mother and baby, starting in pregnancy and developing slowly and gradually. This bonding between mother and child is considered a fundamental adaptation for the preservation of life and constitutes the base of the baby's mental health and of the maternal care. Objective: To determine, through structured instruments, sociodemographic economic cultural and motherhood characteristics and the maternal attachment in the postpartum. Method: It is a correlational analytical descriptive study, using a quantitative methodology. 200 postpartum women were interviewed from January to February 2014, at the Children's Hospital and Maternity of São José do Rio Preto-SP through a structured questionnaire and a validated instrument. Results: The type of delivery by the pregnant woman during prenatal care did not influence the maternal bonding, the undesirability of the pregnancy influenced negatively and, different from the expected, the companion during childbirth did not influence the binding. Conclusion: It is hoped with this study a change in nursing practice, aiming at an improvement in the practice of care, strengthening the relationship between mother/baby and the quality of the spent care by parents to this new being in development.